Women’s Knowledge Of Menopause In Primary Health Care Settings: A Descriptive Cross-Sectional Study In Baregbeg - Yudita Ingga Hindiarti; Arifah Septiane Mukti; Kurniati Devi Purnamasari; Ririn Lestari (Journal of Midwifery and Public Health, 2025)
Background: Menopause is a physiological phase characterized by the permanent cessation of menstruation and is often accompanied by physical and psychological changes requiring women’s preparedness. Adequate knowledge plays an important role in improving readiness and health behaviors during menopause. Objective: This study aimed to describe women’s knowledge about menopause in the working area of Baregbeg Public Health Center. Methods: A descriptive quantitative study with a cross-sectional approach was conducted. The sample consisted of 15 women selected using total sampling. Data were collected using a questionnaire and analyzed through univariate analysis. Results: Most respondents had moderate knowledge (53.3%), followed by poor knowledge (26.7%) and good knowledge (20.0%). Conclusion: Women’s knowledge about menopause remains at a moderate level and requires improvement through structured health education programs in primary health care settings.